2022
DOI: 10.1038/s41562-022-01292-z
|View full text |Cite
|
Sign up to set email alerts
|

The cultural evolution of love in literary history

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 92 publications
2
25
0
Order By: Relevance
“…Finally, behavioral sciences have shown that some cognitive preferences adaptively vary in response to changes in the local environment, especially changes in the level of resources ( Frankenhuis et al, 2016 ; Pepper and Nettle, 2017 ; Baumard, 2019 ; de Courson and Baumard, 2019 ; Mell et al, 2019 ; Boon-Falleur et al, 2020 ; De Courson and Nettle, 2021 ). For instance, higher levels of affluence, predictability and safeness makes people more future-oriented ( Mell et al, 2019 ; Boon-Falleur et al, 2020 ; Guillou et al, 2020 ), more optimist ( Nettle, 2012 ; Inglehart, 2020 ), more cooperative ( Baumard, 2019 ; Jacquet et al, 2019 ), more tolerant ( Inglehart, 2018 ), more romantic ( Baumard et al, 2021 ; Martins and Baumard, 2021 ), and more explorative ( Eliassen et al, 2007 ; Maspons et al, 2019 ; Gopnik, 2020 ). Improvements of living standards in human history, and in a wide range of different cultures, have indeed re-shaped many preferences in directions that are very consistent with this evolutionary account.…”
Section: The Cultural Evolution Of Fictionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, behavioral sciences have shown that some cognitive preferences adaptively vary in response to changes in the local environment, especially changes in the level of resources ( Frankenhuis et al, 2016 ; Pepper and Nettle, 2017 ; Baumard, 2019 ; de Courson and Baumard, 2019 ; Mell et al, 2019 ; Boon-Falleur et al, 2020 ; De Courson and Nettle, 2021 ). For instance, higher levels of affluence, predictability and safeness makes people more future-oriented ( Mell et al, 2019 ; Boon-Falleur et al, 2020 ; Guillou et al, 2020 ), more optimist ( Nettle, 2012 ; Inglehart, 2020 ), more cooperative ( Baumard, 2019 ; Jacquet et al, 2019 ), more tolerant ( Inglehart, 2018 ), more romantic ( Baumard et al, 2021 ; Martins and Baumard, 2021 ), and more explorative ( Eliassen et al, 2007 ; Maspons et al, 2019 ; Gopnik, 2020 ). Improvements of living standards in human history, and in a wide range of different cultures, have indeed re-shaped many preferences in directions that are very consistent with this evolutionary account.…”
Section: The Cultural Evolution Of Fictionsmentioning
confidence: 99%
“…Under the same rationale as we used for other sources of variability (that producers make fictions that please their audience at a given time, in a given location), we propose that adaptive phenotypic plasticity is a major causal explanation for the cultural evolution of fictions across time (in diachrony) and for the cultural distribution of fictions across countries or regions of the world (in synchrony). For instance, in more affluent societies, across both time and space, humans produced fictions with more romantic love stories ( Baumard et al, 2021 ; Martins and Baumard, 2021 ), more cooperative relationships ( Martins and Baumard, 2020 ), and more imaginary worlds ( Dubourg et al, 2021a ). This is the case because such elements tap into preferences that are more evoked in affluent environments.…”
Section: The Cultural Evolution Of Fictionsmentioning
confidence: 99%
See 3 more Smart Citations